2020
DOI: 10.1016/j.prro.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A Cancer Care Ontario Organizational Guideline for the Delivery of Stereotactic Radiosurgery for Brain Metastasis in Ontario, Canada

Abstract: In Ontario, Canada, there is increasing demand for stereotactic radiosurgery (SRS) for brain metastases. Recommendations for safe SRS delivery are needed to ensure that patients receive an equitable level of care across the province. This guideline presents the minimal recommendations for the organization and delivery of SRS with respect to the multidisciplinary team, applicable technologies, imaging requirements, quality assurance program, and patient follow-up. Methods and Materials: The recommendations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In 2010, Ammirati et al showed that there were insufficient data to make clear recommendations for the management of local recurrent or distant BMs [38]. Today, salvage and repeated SRT has become an accepted standard of care in the treatment of a limited number of new BMs [39,40]. Nevertheless, the definition of limited brain diseases…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Ammirati et al showed that there were insufficient data to make clear recommendations for the management of local recurrent or distant BMs [38]. Today, salvage and repeated SRT has become an accepted standard of care in the treatment of a limited number of new BMs [39,40]. Nevertheless, the definition of limited brain diseases…”
Section: Discussionmentioning
confidence: 99%
“…A protocolized and evergreen quality assurance program is needed at both the departmental level and a patient-specific level (72) For patient-specific QA, target volume delineation should ideally undergo peer review prior to treatment (especially for complex targets such as resection cavities), and pre-treatment verification using film dosimetry is highly recommended (73)(74)(75)(76) Non-modifiable factors including: (I) intrinsic radiosensitivity;…”
Section: Lack Of Quality Assurance (Qa) Programmentioning
confidence: 99%